The defeat of Barisan Nasional missed signs or late surge? - Hutchinson, Francis E.; Hutchinson, Francis E.; Lee, Hwok Aun; Lee, Hwok Aun; Hu, Benjamin K. H.; Pang, Pearlyn Y. (ISEAS Yusof Ishak Institute, 2019)
The results of Malaysia's 14th General Elections of May 2018 were unexpected and transformative. Against conventional wisdom, the newly reconfigured opposition grouping Pakatan Harapan (PH) decisively defeated the incumbent Barisan Nasional (BN), ending six decades of uninterrupted dominant one-party rule. Despite a long-running financial scandal dogging the ruling coalition, pollsters and commentators predicted a solid BN victory or, at least, a narrow parliamentary majority. Yet, on the day, deeply rooted political dynamics and influential actors came together, sweeping aside many prevailing assumptions and reconfiguring the country's political reality in the process. In order to understand the elections and their implications, this edited volume brings together contributions from ISEAS - Yusof Ishak Institute researchers and a group of selected collaborators to examine the elections from three angles: campaign dynamics; important trends among major interest groups; and local-level dynamics and developments in key states. This analytical work is complemented by personal narratives from a selection of GE-14 participants.